An atomic force microscopy study of calcite dissolution in saline solutions: The role of magnesium ions - Ruiz-Agudo, E.; Putnis, Christine; Jiménez-López, C.; Rodriguez-Navarro, C. (Pergamon, 2009)
In situ Atomic Force Microscopy, AFM, experiments have been carried out using calcite cleavage surfaces in contact with solutions of MgSO4, MgCl2, Na2SO4 and NaCl in order to attempt to understand the role of Mg2+ during calcite dissolution. Although previous work has indicated that magnesium inhibits calcite dissolution, quantitative AFM analyses show that despite the fact that Mg2+ inhibits etch pit spreading, it increases the density and depth of etch pits nucleated on calcite surfaces and, subsequently, the overall dissolution rates: i.e., from 10-11.75 mol cm-2 s-1 (in deionized water) up to 10-10.54 mol cm-2 s-1 (in 2.8 M MgSO4). Such an effect is concentration-dependent and it is most evident in concentrated solutions ([Mg2+] >> 50 mM). These results show that common soluble salts (especially Mg sulfates) may play a critical role in the chemical weathering of carbonate rocks in nature as well as in the decay of carbonate stone in buildings and statuary. © 2009 Elsevier Ltd. All rights reserved.